2022
DOI: 10.1002/fee.2458
|View full text |Cite
|
Sign up to set email alerts
|

Arresting the spread of invasive species in continental systems

Abstract: Invasive species are a primary threat to biodiversity and are challenging to manage once populations become established in previously unoccupied areas. But removing them is further complicated when invasions occur in continental, mixed‐ownership systems. We demonstrate a rare conservation success: the regional‐scale removal of an invasive predator – the barred owl (Strix varia) – to benefit the spotted owl (Strix occidentalis) in California. Barred owl site occupancy declined sixfold, from 0.19 to 0.03, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Experimental studies conducted in the Pacific Northwest and Sierra Nevada have demonstrated that lethal removals can substantially reduce barred owl densities and alleviate well-documented competitive pressures on native spotted owls (Diller et al, 2014; Wiens et al, 2021; Hofstadter et al, 2022). Our results suggest that removals conducted to promote the recovery of spotted owls may also benefit a broad range of additional vertebrate species consumed by invasive barred owls.…”
Section: Management Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental studies conducted in the Pacific Northwest and Sierra Nevada have demonstrated that lethal removals can substantially reduce barred owl densities and alleviate well-documented competitive pressures on native spotted owls (Diller et al, 2014; Wiens et al, 2021; Hofstadter et al, 2022). Our results suggest that removals conducted to promote the recovery of spotted owls may also benefit a broad range of additional vertebrate species consumed by invasive barred owls.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Our results suggest that removals conducted to promote the recovery of spotted owls may also benefit a broad range of additional vertebrate species consumed by invasive barred owls. While barred owl populations have been reduced to very low densities throughout the range of the California spotted owl in the Sierra Nevada (Hofstadter et al, 2022), removal areas only encompass a small portion of the range of the northern spotted owl in California, Oregon, and Washington (Wiens et al, 2021). Without expanding current efforts, barred owl populations will inevitably continue to grow outside of the limited footprints of these areas.…”
Section: Management Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, barred owls are now considered an existential threat to spotted owls, with formerly large populations of spotted owls functionally extirpated (Gutiérrez et al, 2007;Wiens et al, 2021). In response, experimental removals of barred owls have been conducted at local scales in the range of the northern spotted owl (Diller et al, 2014;Wiens et al, 2021), and region-wide experimental removals have effectively reduced the population of barred owls in the Sierra Nevada (Hofstadter et al, 2022).…”
Section: Introductionmentioning
confidence: 99%